ANALISIS HUBUNGAN MODEL PEMBELAJARAN DIRECT INSTRUCTION DENGAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN PAI (Studi Survei di SMA Negeri 106 Jakarta) - Muhammad Faishal; Yuli Marlina; Kunaenih; Muhammad Rizal Mantovani; Fauzan Kumarsanuh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of critical thinking skills in Islamic Religious Education (PAI) learning and the continued dominance of the Direct Instruction learning model in schools. This model is effective in delivering material systematically and in a structured manner, but its relationship with students' critical thinking skills still needs to be examined. This study aims to determine the relationship between the Direct Instruction learning model and students' critical thinking skills in PAI learning at SMA Negeri 106 Jakarta. The study used a quantitative method with a correlational survey approach. Data were collected through questionnaires, observation, interviews, and documentation. The research sample consisted of 89 students selected using simple random sampling technique. Data were analyzed using descriptive statistics and the Pearson Product Moment correlation test with IBM SPSS. The results showed a significant relationship between the Direct Instruction learning model and students' critical thinking skills, with a correlation coefficient (r) of -0.213 and a significance value (Sig.) of 0.045 < 0.05. Thus, Ha is accepted and H0 is rejected. The correlation coefficient indicates that the relationship between the two variables is weak and negative in direction, meaning that the higher the application of the Direct Instruction model, the lower students' critical thinking ability tends to be. However, interview results indicate that Direct Instruction still plays a role in building basic conceptual understanding before students develop critical thinking skills through more student-centered learning strategies.